Dampak Aktivitas Manusia terhadap Kualitas Air Sungai Wariori di Kabupaten Manokwari, Provinsi Papua Barat - Ahmad; Raharjo, Syafrudin; Taher, Achmad (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
The purpose of this study is to show how the Wariori River in Manokwari Regency is polluted as a result of illegal gold mining operations, oil palm plantations, C-type mining, settlements, and other uses of forest resources. During the dry and wet seasons, five observation locations along the river provide air quality data that is used to calculate the pollution index (IP). The results of the study show that human activity has had a major impact on the Wariori River's water quality. All water quality parameters, including pH, dissolved oxygen (DO), chemical oxygen demand (COD), biochemical oxygen demand (BOD), NO3, and total coliform, have generally not exceeded the quality standards set by Government Regulation No. 22 of 2021, with the exception of two parameters: total suspended solids (TSS) and total phosphate. Significant erosion and sedimentation are indicated by high TSS readings during the wet season. According to the findings of the research conducted using the Pollution Index (IP), all places in the water quality data have a polluted state for both seasons. This study highlights the need for more stringent environmental management and conservation initiatives to lessen the damaging effects of human activity on the ecosystem of the Wariori River.